BMT AL - ITTIHAD STRATEGY TO FACE COMPETITION - Nofrizal Nofrizal (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
This research aims to formulate and select the BMT Al-Ittihad Rumbai strategy to face the changing competition of business environment the are from internal environment such as organization resources, finance, member and external business such as competitor, economy, politics and others. Method of this research used Analysis of EFAS, IFAS, IE Matrix, SWOT-8K Matrix, SPACE Matrix and TWOS Matrix. Our hope from this research, it can assist BMT Al-Ittihad in formulating and selecting strategies for the sustainability of BMT Al-Ittihad in the future. The sample in this research is using purposive sampling technique that is the manager and leader of BMT Al-Ittihad Rumbai Pekanbaru. The result of this research shows that the position of BMT Al-Ittihad using IE Matrix, SWOT-8K Matrix and SPACE Matrix is in growth position, stabilization and aggressive. The choice of strategy after using TWOS Matrix is market penetration, market development, vertical integration, horizontal integration, and stabilization (careful.)Keyword: internal environment, external environment, strategy formulation, TWOS Matrix